Small and medium enterprises’ approach towards CSR: Empirical study - Bachnik, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
SMEs face a challenge of responding to inescapable changes as a result of various internal and external factors. As they attempt to cope with the changing conditions, they might face attitudinal and behavioral shifts. They need to develop new ways of thinking about their operations and dealing with various groups of stakeholders. Adoption of more sustainable approach might contribute to the success of a company in terms of cost impact, innovation impact, environmental impact and stakeholder impact. The aim of the article is to define the degree to which SMEs understand ideas behind corporate social responsibility (CSR) and to determine the degree of maturity of SMEs with regard to CSR. Of particular interest is to identify the dimensions of CSR engagement and to verify which component: social, environmental or economic, plays a dominant role for SMEs, which will further inform about the fact whether CSR has operational or rather strategic character. The article presents selected results of empirical research conducted by the Institute of Management at Warsaw School of Economics in 2016
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 464, s. 9-19
Keywords: SME; CSR